Auto-Backlund transformations and New Exact Soliton Solutions of KdV Equation for Nonlinear Dust Acoustic Solitary Waves in Dust Plasma with Variable Dust Charge - Ibrahim, Rafat (International Journal of Applied Mathematical Research, 2014)
The nonlinear properties of dust acoustic solitary waves in unmagnetized dust plasma consistingof negative charged dust particles , Boltzmann distributed electrons and non-thermal distributedions with variable dust charge are investigated. By using the reductive perturbation theory, a Korteweg-de Veries (KdV) equation is derived. The Sagdeev’s potential are obtained in terms ofion acoustic velocity by using the auto-Backlund (BT) transformation, the modified G'/G expansion,the sine-cosine expansion method, the sinh-coshine expansion method, and the sech-tanh expansionmethod describing the nonlinear propagation of ion-acoustic solitary waves in unmagnetized dustplasma. Keywords: dust plasma, KdV equation, Reductive perturbation method, solitary waves, BÄ acklund transformations, Traveling wave solutions.